Plastic film mulch changes the microbial community in maize root-associated compartments - Li, Yüze; Li, Tong; Wang, Ziting; Wang, Shengnan; Qin, Xiaoliang; Liao, Yuncheng (Plant and soil, 2022)
Aims Plastic film mulch (PFM) was an important agricultural measure to promote crop production. It is important to reveal the patterns of root-associated microbiomes under PFM to enhance the basic knowledge in the agroecosystem. Methods The microbial composition, assembly, and co-occurrence in four compartments (bulk soil, root zone, rhizosphere, and rhizoplane) under maize field adopting PFM and flat planting were analyzed at the V12 stage. The root phenotypic traits were measured to explore their interaction mechanisms with microbes. Results The compartment was the dominant factor shaping the bacterial communities, while fungal communities were recruited by treatment. With a variety of plant growth-promoting abilities, bacteria order SBR1013, S085, genera Aquicella , and fungi family Aspergillaceae , Laslosphaeriaceae , Hypocreaceae were identified significantly enriched by PFM across all compartments. PFM harbored a more stable and complex co-occurrence network than that of flat planting, and the Chitinophagales with the ability to utilize recalcitrant carbon was the keystone taxa while they were Sphingomonadales under flat planting. Root traits were found closely related to root-associated microbiomes, and interkingdom networks further revealed that the relationships between rhizoplane microbes and root weight/root length density were greatly enhanced by PFM compared to flat planting. Conclusions PFM changed maize root traits and assembly, composition, and co-occurrence patterns of root-associated microbiomes, recruited specific taxa potentially benefit to plant growth. The interactions of root traits and microbes were strengthened by PFM. These findings enhanced understanding of root-soil interactions in the agroecosystem.